Preparation and characterization of Ni–TiO2 composites electrodeposited from an ethylene glycol-based deep eutectic solvent. (2022) - Protsenko, V.S.; Butyrina, T.E.; Bobrova, L.S.; Danilov, F.I.
Abstract: Ni–TiO2 composite electrolytic deposits were fabricated from an electrolyte based on ethylene glycol-containing deep eutectic solvent (the so-called ethaline, which is a typical representative of a new generation of room temperature ionic liquids). The electrolyte contained dissolved nickel (II) chloride salt and the addition of water that ensures an increase in electrical conductivity, a decrease in viscosity, and an increase in the content of the dispersed TiO2 phase in the coating (up to 10 wt%). The influence of the content of water and titanium dioxide in the electrolyte on the composition of the composite coating has been investigated. X-ray phase analysis and study of surface morphology (by scanning electron microscopy) were carried out. An increase in the electrocatalytic activity in the reaction of hydrogen evolution was detected, which was explained by the introduction of particles of the TiO2 dispersed phase into the electrodeposited nickel matrix.